Pesan Motivasi Meraih Cita-Cita pada Lagu "Hello Future" Karya NCT Dream - Raden Nisrina Aulia Indallah; Ferry Darmawan (Bandung Conference Series: Communication Management, 2023)
Abstract. Music is one of the works of art humans have long known, and music can make listeners feel comfortable and happy. Music can also motivate or encourage someone in activities that help listeners achieve goals in social, language, or motor functions. As is the case with NCT Dream's song "Hello Future," which has a motivational meaning for listeners. Motivation meaning can be obtained from a song because the song is a one-way communication from the songwriter to the listener. That makes researchers research motivation's meaning using semiotic methods that study signs. Therefore this research involves the theory of symbolic interaction communication, Ferdinand de Saussure's theory of semiotics, the learning theory as motivation, and the concept of song as motivation. The results of this study on the NCT Dream song "Hello Future" are that there is a motivational meaning in it through signs from Ferdinand De Saussure's theory and symbolic interaction because it emphasizes the relationship of motivation with reaching for the future through symbols and interactions. There is motivation because the listener catches the symbols provided by songwriters and developing them. The ability of listeners to reflect on themselves through other people's opinions or points of view, so that individuals can create networks of social relations. The conclusion of this study is to motivate listeners to achieve dreams according to what they want for the future, and this song motivates listeners to be optimistic in undergoing the process towards the future, besides that the results of this study have significant relationships that are interrelated so that they show motivating meanings. Abstrak. Musik merupakan salah satu dari karya seni yang sudah lama dikenal oleh manusia, musik dapat membuat pendengarnya merasa senang, nyaman, dan gembira. Musik juga mampu menjadi motivasi atau mendorong seseorang seseorang dalam kegiatan yang membantu pendengarnya dalam meraih tujuan dalam fungsi sosial, bahasa atau motorik. Seperti halnya pada lagu NCT Dream “Hello Future” yang memiliki makna motivasi bagi para pendengarnya. Dari hal tersebut makna motivasi bisa didapat dari sebuah lagu, karena lagu merupakan komunikasi satu arah dari pencipta lagu kepada pendengarnya, hal ini membuat peneliti membuat penelitian mengenai makna motivasi yang menggunakan metode semiotika yang mempelajari mengenai tanda-tanda, maka dari itu penelitian ini melibatkan teori komunikasi interaksi simbolik, teori semiotika Ferdinand de Saussure, teori belajar sebagai motivasi, dan konsep lagu sebagai motivasi. Hasil dari penelitian ini pada lagu NCT Dream “Hello Future” yaitu terdapat makna motivasi didalamnya melalui tanda penanda dari teori Ferdinand De Saussure, dan interaksi simbolik karena menekankan hubungan motivasi dengan meraih masa depan melalui simbol dan interaksi, dan adanya termotivasi karena pendengar menangkap simbol-simbol yang diberikan oleh pencipta lagu dan mengembangkannya, dan kemampuan pendengar dalam merefleksikan dirinya melalui pendapat orang atau sudut pandang orang lain, sehingga individu dapat menciptakan jejaring hubungan sosial. Kesimpulan penelitian ini yaitu memotivasi para pendengarnya untuk meraih mimpi sesuai dengan yang mereka inginkan untuk masa depannya, dan lagu ini memotivasi pendengarnya untuk optimis dalam menjalani proses menuju masa depan, selain itu hasil penelitian ini memiliki relasi tanda yang saling berkaitan sehingga menunjukan makna-makna memotivasi.